Planned Neighborhoods, Planned Cities and Strategic Digital City: Cases around the World with Posthumanism Approaches - Rezende, Denis Alcides; Al Lahham, NourAllah; Bahmanfar, Hanyeh; Okon, Godswill Udoh (Journal of Posthumanism, 2025)
The objective is to analyze the relationships between planned neighborhoods, and planned cities in the strategic digital city context, considering city posthumanism approaches. Through case studies’ method of British New Towns, Songdo, Shiraz, Manaus, Konstanz, Cairo, and Lagos, the research methodology employs qualitative and quantitative techniques to analyze planning strategies, socio-economic and environmental impacts. Results show that planned neighborhoods and cities successfully foster social cohesion and economic resilience. However, they face challenges in inclusivity and adapting to rapidly changing technologies. Strategic digital cities offer significant potential by integrating technology to improve urban management but must address inequities and governance gaps. The conclusion emphasizes that adaptive governance and participatory frameworks are essential for achieving equitable and sustainable urban development. By combining traditional urban planning principles with digital innovations, these approaches can shape resilient, inclusive, and technologically integrated cities with posthumanism, because in digital cities, human beings do not effectively exist.